A Study on Work-Life Balance of Working women With Special Reference to Sangli District: An Educational Perspective - Yadav, Pallavi Shrirang; Jadhav, Sudarshan Dhairyasheel (ASEAN Journal of Educational Research and Technology, 2023)
A woman plays various roles in her life. She faces many difficulties while dealing with every situation in her life. When a woman is a working woman, she needs to balance her personal life as well as her professional life. She faces a lot of hurdles during these phases. In the early centuries, we used to see most of the women were seen in the kitchens and the women which used to work where been in the factories, on the farm, or used to work in shops. But due to the increasing literacy rate in society and also the literacy rate of women has increased, they come out of their regular activities and look forward to being successful in their professional life. In the early days, the work of a woman was just to see after her family and fulfil her family responsibilities.